Hubungan Antara Minat Menggunakan Fashion Korea Di Instagram Dengan Perilaku Impulsive Buying - Putri, Afifah Javanda; Tayo, Yanti; Nurkinan, Nurkinan (Peneliti.net, 2023)
Popular culture arises in the midst of people's lives in various forms, such as from what people consume, what people see, what people watch, what people listen to, and what people wear. Popular culture sulks at the popularity of Korean entertainment and culture in other countries such as Korean Pop and Korean fashion. This study aims to determine whether there is a relationship between interest in using Korean fashion on Instagram with impulsive buying behavior in UNSIKA Communication Science students 2020 by looking at 2 indicators, visibility and attractions. This study used a quantitative approach with simple linear regression analysis, and with the support of Uses and Effect theory. Data collection techniques in this study used questionnaires and literature studies. The results of this study found that the visibility of Korean fashion has a relationship between interest in using Korean fashion with impulsive buying behavior, and also Korean fashion attractions and the use of fashion by Korean idols has a relationship between interest in using Korean fashion with impulsive buying behavior.